Addressing digital religious polarization: Policy analysis of religious moderation narratives on Indonesian government social media - Ach Barocky Zaimina (Al'Adalah, 2025)
This article examines how Indonesian state institutions construct and communicate narratives of religious moderation in a contested digital public sphere. Focusing on the Ministry of Religious Affairs (MoRA) and the National Counter-Terrorism Agency (BNPT), the study employs a descriptive qualitative design that integrates digital observation of official Instagram, X/Twitter, and YouTube accounts from January to December 2024, analysis of policy documents and institutional reports, and semi-structured interviews with policymakers and social-media administrators. Data are analysed through content and framing analysis, as well as interview-based thematic coding with triangulation. Findings indicate that state messaging is dominated by normative, declarative, and largely one-way communication, which is associated with weaker dialogic engagement and recurrent scepticism in comment spaces. By contrast, personal testimonies, lived-experience narratives, and non-patronising visual rhetoric receive more favourable reactions and lower resistance. Emotional appeal, contextual relevance, and a personal approach emerge as key determinants of constructive uptake, whereas limited responsiveness and broadcast-style posting amplify disengagement. The article links these reception patterns to post-truth dynamics and conceptualises monologic digital communication as a governance effect. It concludes that participatory public diplomacy, centred on co-creation with trusted intermediaries and institutionalised listening, provides an operational pathway to strengthen digital religious resilience.